Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/jfb.12026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trawling on the diets of common demersal fish by‐catch of a tropical prawn trawl fishery

Abstract: The ecological effect of prawn trawling on the benthos of the Gulf of Carpentaria, northern Australia, was investigated by examining stomach contents of common demersal fishes incidentally caught as by-catch in the fishery. Fishes were collected from high and low fishing intensity sites in three regions based on vessel monitoring system data. The diets of eight species of benthic fish predators were compared between regions and fishing intensities. A regional effect on diet was evident for seven species. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
1
7
0
3
Order By: Relevance
“…In relation to trawl intensity the two species showed a highly opportunistic feeding strategy and co-occurred at all sites by showing differences in their diet preferences (Ribi et al, 1977) and shifting in size-frequency distributions. Our results support the hypothesis that bottom trawling affects the fitness of benthivorous organisms by altering the food availability and generating a positive response of facultative scavengers to carrion (Demestre et al, 2000;Link, 2004;Dell et al, 2013;Johnson et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In relation to trawl intensity the two species showed a highly opportunistic feeding strategy and co-occurred at all sites by showing differences in their diet preferences (Ribi et al, 1977) and shifting in size-frequency distributions. Our results support the hypothesis that bottom trawling affects the fitness of benthivorous organisms by altering the food availability and generating a positive response of facultative scavengers to carrion (Demestre et al, 2000;Link, 2004;Dell et al, 2013;Johnson et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Here, we tested the hypothesis that bottom trawling affects the diet of benthivorous organisms by altering food availability and generating a positive response of facultative scavengers to carrion. Benthic scavengers feeding on the benthic community that results from the effects of trawling might represent costeffective samplers, hence diet studies may provide insights into the trophic consequences of such community changes for other components of the ecosystem (Link, 2004;Dell et al, 2013;Johnson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, these fish had reduced body condition, which is most likely explained by the additional energetic costs of searching for food in a reduced prey field. Dell et al (2013) also found differences in the composition of the diet of eight fish species between low and high fishing intensity areas in a tropical prawn fishery, and also found that stomach fullness did not differ between low and high trawling areas.…”
Section: Effects Of Bottom Trawling On Fish Prey Resourcesmentioning
confidence: 73%
“…Dell et al . () also found differences in the composition of the diet of eight fish species between low and high fishing intensity areas in a tropical prawn fishery, and also found that stomach fullness did not differ between low and high trawling areas.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation